DINAMIKA KEHIDUPAN MANUSIA DAN KONDISI SUMBERDAYA ALAM DAERAH ALIRAN SUNGAI (JURNAL SPASIAL, 2016)
The purpose of writing this article is to give an overview of watershed damage that has occurred, which also led to the occurrence of natural disasters. Watershed damage that occurs due to the interaction between human and natural resources show that the interaction is negative in the end will result in damage and natural disasters. This paper is a literature review on the analysis of the facts that occurred on the field of natural resource conditions watersheds, as well as in the analysis of the theories associated with pegelolaan DAS. Based on the problems and phenomena of watershed degradation that has occurred in recent years, it is necessary efforts and strategies for watershed management that are useful for the realization of the sustainability of the watershed for the present and future. Cooperation between the public and the government in watershed management is the key factor required. The government must be able to move the various stakeholders in the management of natural resources, including natural resources watersheds, through policies, strategies, and programs to both short term and long term.Keywords: dynamics, human, watershed resources.